2017
DOI: 10.1111/jfbc.12410
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile compounds as quality indicators for Fuji apples after cold storage

Abstract: Changes in the volatile components in Fuji apples were investigated by the analysis of intact apples using headspace solid‐phase microextraction–gas chromatography–mass spectrometry to assess their quality during long‐term storage at 4°C (3, 6, and 9 months). Three alcohols and 28 esters were identified, and the feeding of precursor alcohols (e.g., butanol, hexanol, and 2‐methylbutanol) resulted in significantly increased amounts of eight esters. Among these esters, the peak area ratios (PARs) of butyl acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…2-Furanmethanol, also known as furfuryl alcohol, is a flavoring ingredient. Hexyl acetate (apple flavor) is produced by the esterification of acids with alcohols, [30] and Lee et al [31] reported that the alcohol contents depended on acidity, with the majority being ethanol and 1-hexanol. Therefore, these SPME-Arrow-extracted VOCs contribute to the assessment and characterization of brown rice vinegar quality.…”
Section: Comparing the Spme-arrow And Conventional Spme Methodsmentioning
confidence: 99%
“…2-Furanmethanol, also known as furfuryl alcohol, is a flavoring ingredient. Hexyl acetate (apple flavor) is produced by the esterification of acids with alcohols, [30] and Lee et al [31] reported that the alcohol contents depended on acidity, with the majority being ethanol and 1-hexanol. Therefore, these SPME-Arrow-extracted VOCs contribute to the assessment and characterization of brown rice vinegar quality.…”
Section: Comparing the Spme-arrow And Conventional Spme Methodsmentioning
confidence: 99%
“…At last, 120 and 105 samples were collected from Shandong and Xinjian region (the SSC of the bagged stripped Xinjiang samples were all below 15°Brix), respectively. The samples were stored in cabinet at 4 °C and 75% relative humidity (RH) according each classification after transported back to the laboratory (Lee et al 2017).…”
Section: Sample Preparation and Treatmentsmentioning
confidence: 99%
“…analysis (Janho et al 2017), which can achieve dynamic monitoring. However, the aroma of the pulp cannot be fully obtained, due to the barrier function of the peel.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods need large amounts of extraction solvents, have low recovery, and can be used only with low-fat samples. To offset these disadvantages, headspace extraction methods such as dynamic headspace (DHS) [ 18 ], headspace solid-phase microextraction (HS-SPME) [ 19 ], and headspace stir-bar sorptive extraction (HS-SBSE) [ 20 , 21 ] are widely used. Headspace extraction methods do not need organic solvents and they can be applied with even small amounts of samples.…”
Section: Introductionmentioning
confidence: 99%